2022
DOI: 10.3390/cells11182788
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine Ameliorates MIA-Induced Impairment of Sensorimotor Gating: Focus on Neuron-Microglia Communication and the Inflammatory Response in the Frontal Cortex of Adult Offspring of Wistar Rats

Abstract: The maternal immune activation produced by the systemic administration of lipopolysaccharide (LPS) in rats provides valuable insights into the basis of behavioural schizophrenia-like disturbances and biochemical changes in the brains of the offspring, such as microglial activation. Regarding therapy, antipsychotics continually constitute the cornerstone of schizophrenia treatment. To their various efficacy and side effects, as well as not fully recognised mechanisms of action, further characteristics have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 132 publications
1
5
0
Order By: Relevance
“…In rats after basolateral amygdala lesions generated using quinolinic acid [13], as well as in a rodent model based on prenatal exposure to polyinosinic-polycytidylic acid [14], quetiapine normalized deficits in prepulse inhibition of sensorimotor gating. A similar phenomenon was reported for rat offspring subjected to lipopolysaccharide (LPS) in the prenatal period [15]. Furthermore, treatment with quetiapine attenuated behaviours resembling this neurological condition (e.g., hyperactivity, spatial working memory impairments and sensorimotor gating deficits) in MK-801-injected mice [16].…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…In rats after basolateral amygdala lesions generated using quinolinic acid [13], as well as in a rodent model based on prenatal exposure to polyinosinic-polycytidylic acid [14], quetiapine normalized deficits in prepulse inhibition of sensorimotor gating. A similar phenomenon was reported for rat offspring subjected to lipopolysaccharide (LPS) in the prenatal period [15]. Furthermore, treatment with quetiapine attenuated behaviours resembling this neurological condition (e.g., hyperactivity, spatial working memory impairments and sensorimotor gating deficits) in MK-801-injected mice [16].…”
Section: Introductionsupporting
confidence: 73%
“…To date, data concerning the anti-inflammatory action of quetiapine have varied and depended on the experimental model used, the dose and the administration method of the drug. Previously published reports underlined a doubleedged immunomodulatory mechanism of this antipsychotic [15], which could be crucial in the context of the efficacy of quetiapine, as it was also influenced by the prior inflammatory activation state of cells [84]. Thus, the modulatory potential of quetiapine might be related to the inhibition of pro-inflammatory response rather than the stimulation of its antiinflammatory components.…”
Section: Quetiapine Exerts Immunomodulatory Effects In Organotypic Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of microglial proton currents is also involved in the anti-inflammatory effect of clozapine and does not involve serotonin receptors. 91 Moreover, in vivo studies showed that clozapine can regulate microglial activation in a model of chronic experimental autoimmune encephalomyelitis, 92 while quetiapine modulates brain inflammatory processes in adult rats prenatally exposed to lipopolysaccharide (LPS), a model of schizophrenia-like disturbances, 93 and in a transgenic mice model of Alzheimer's disease. 39 With regard to typical antipsychotics, chlorpromazine and haloperidol have been demonstrated to exert some anti-inflammatory effects in microglial cells, 90,94 also by decreasing the release of pro-inflammatory cytokines.…”
Section: Glial Cells As Targets Of Antipsychoticsmentioning
confidence: 99%